WAYS OF INTENSIFICATION OF ENGLISH TEACHING FOR FUTURE GRADUATES OF NON-LANGUAGE SPECIALTIES - Sarkisova, A.; Luchentsova, I. (Problems of Engineer-Pedagogical Education, 2021)
Ukraine's rapid entry into the world community, economic and socio-cultural situation in the country ensured a huge demand for knowledge of foreign languages and created a powerful motivational base for their study. At the present stage, the main priority of which is the expansion of Ukraine’s international ties and contacts in various spheres of life, there is a need for professionally oriented communication with foreign colleagues. The article proposes ways to intensify the teaching of English for future non-native language graduates. It addresses the current problems of improving the learning process for maximum results. After all, this issue requires a radically new approach to solving it, since the pace of economic development requires high-level foreign language graduates from higher education. The foreign language teacher should understand that the modernization involves: firstly, changes in the goals and the result of learning, secondly, reduction of the content required for the development of content, third, changes in methods and technologies for mastering the minimized content of training, fourth, individualization of the process of learning a foreign language, fifth, change of standards, curriculum in a foreign language. The teacher must remember that it is necessary to modernize the scientific and theoretical approach to teaching a foreign language. The combination of methods of intensifying the teaching of a foreign language allows to elevate the learning process to a new level, promotes better students' knowledge, encourages them to deepen the discipline. In the future, it is planned to analyze more detaily the role of computer technology in intensifying the learning process. increase the efficiency of the educational process; provides students with the opportunity to study at a convenient time for them; provides a variety of forms, methods, tools and modes of learning; increases students' motivation; allows to carry out self-control of own educational activity; promotes self-education and self-development of students. By the efficiency of the educational process we understand the degree of achievement of the set goal of pedagogical activity taking into account the optimality of the spent efforts, means and time.